CONTACT – communication protocol for family practitioners and specialists - Sobczak, Krzysztof; Janaszczyk, Agata; Leoniuk, Katarzyna (Journal of Medical Science, 2017)
Introduction. Ability to gather and process medical data serves as a basic tool of doctor’s work, which can be improved by applying communication protocols. In most cases, however, instructions presented by such models are too general and do not take into account patients’ preferences. Material and Methods. The study was carried out in the form of an electronic questionairre sent to a randomly chosen group of adult patients (N = 967). It consisted of close-ended questions about the quality of communication skills of family practitioners and specialists working at outpatient clinics and health centers.  Results. Only 21% of patients claimed that the appointment started on time. 51% mentioned disruptions during the meeting, mainly by a third party (34%). A considerable majority of physicians carried out the interview in a manner that was understood by patients, nevertheless 56.6% of the respondents felt underinformed as far as the nature of their illness was concerned – these objections were mostly expressed by patients suffering from chronic diseases. Conclusions. Our research shows that a proper organization of work as well as observing the principles of appropriate clinical communication can facilitate doctors’ performance, and thus increase both the level of patients’ satisfaction and the quality of medical services.
Keywords: communication and interview skills; clinical-patient communication/relationship; cultural competence/proficiency